Rare bird documentation form for Northern Goshawk at Hickory Hill Park, 1977 - Newlon, Michael C.et al (1977)
Rare bird documentation form for a Northern Goshawk at Hickory Hill Park in Iowa City in Johnson County, IA on September 18, 1977. Epson - sheet feed